Chemotherapy in pancreatic cancer: results of a controlled, prospective, randomised, multicentre trial. Issue 6255 (13th December 1980) - Mallinson, C N; Rake, M O; Cocking, J B; Fox, C A; Cwynarski, M T; Diffey, B L; Jackson, G A; Hanley, J; Wass, V J
Abstract : Forty patients with inoperable pancreatic cancer were included in a prospective, randomised, controlled trial of multiple chemotherapy. The survival of 19 untreated control patients was compared with that of 21 patients who received an initiation course of intravenous fluorouracil, cyclophosphamide, methotrexate, and vincristine given over five days followed by intravenous fluorouracil and mitomycin given over three or five days at six-week intervals thereafter. Median survival in treated patients was 44 weeks, which was significantly longer than the nine weeks seen in controls. In patients without metastases median survival was 48 weeks in the treated group and 12 weeks in controls. In patients with metastases it was 30 weeks in treated patients and seven weeks in controls. The treatment was well tolerated and seemed to confer a significant prolongation of survival, comparing favourably with previous reports of chemotherapy with or without radiotherapy. If the results are confirmed this regimen may be useful in district general hospital practice.